Modulation of p300 binding by posttranslational modifications of the C-terminal activation domain of hypoxia-inducible factor-1 alpha - Cho, Hyunju; Ahn, Dae-Ro; Park, Hyunsung; Yang, Eun Gyeong (ELSEVIER SCIENCE BV, 2007)
Posttranslational modifications of hypoxia-inducible factor-1 alpha (HIF-1 alpha) influence HIF-inediated transcription, likely by affecting binding to p300/cAMP-response element-binding protein (CBP). To systematically analyze the HIF-1 alpha-p300/CBP interaction, we developed a fluorescence polarization-based binding assay, employing fluorescein-labeled peptides derived from the C-terminal transactivation domain (C-TAD) of HIF-1 alpha. After optimized for effectively capturing p300/CBP, the assay was utilized for evaluating direct effects of posttranslational modifications of the HIF-1 alpha C-TAD on p300 binding. The results demonstrated that asparagine hydroxylation and S-nitrosylation of HIF-1 alpha decrease p300 binding, while its phosphorylation does not affect p300 binding, which was reconfirmed by competitive inhibition analyses using mutant peptides. (c) 2007 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.
Keywords: HYPOXIA-INDUCIBLE FACTOR-1-ALPHA; HIF-ALPHA; STRUCTURAL BASIS; PHOSPHORYLATION; HYDROXYLATION; CBP/P300; SIGNAL; TRANSCRIPTION; DIMERIZATION; HIF-1-ALPHA